The changing nature and pattern of intra-party conflict in Nigeria’s fourth republic: critical assessment of All Progressives Congress - Yahaya, Muhammad Aminu (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study is an analysis of the nature and pattern of intra-party conflict in Nigeria’s Fourth Republic with specific reference to the ruling All Progressives Congress (APC). Intra-party conflict has been the norm in Nigerian politics leading to crises, setback and failure of many parties to forge ahead for proper democratisation in Nigeria including the ruling parties in many instances. The problem is the way in which intra-party conflict is becoming the bane of democratisation and good governance in Nigeria for many decades and despite the previous experiences, the phenomenon continued unabated. The study investigated the new dimension of intra-party conflict in Nigeria taking the APC as the case study. The study used a qualitative method of data collection and analysis. Primary and secondary sources of data were used. The primary data involved in-depth interviews with some selected informants from the relevant institutions and agencies related to the APC and the crises such as the national party executives, senior officials of the Independent National Electoral Commission (INEC) and academicians that are experts in the area of study. The secondary sources included were books, journals, newspapers, internets and other documented materials. The data obtained were discussed using content analysis where thematic analytical interpretations were used in the discussions. The research discovered that, the intra-party conflict under the APC has taken a new dimension where the members of the ruling party constituted an opposition and a stumbling block for the party’s progress and governance. The work recommends that intra-party conflict of APC and other Nigerian political parties can be resolved through constitutional reforms, institutionalisation of party ideology and principles as well as strict sanctions from the national party leaders.